RETRACTED: The Effect of Productive Safety Net Programme on Household Food Consumption and Dietary Diversity in Ethiopia - Feyisa, Mebratu Negera (Frontiers in Sustainable Food Systems, 2022)
This study empirically investigates the effect of productive safety net programme (PSNP) on household food consumption and dietary diversity in Ethiopia. The study applied random effects with instrumental variable to estimate the effect of PSNP membership. The study indicates that though PSNP membership improves household food consumption, it reduces household dietary diversity score. Household food consumption and dietary diversity are also significantly influenced by sex, age, education status of household head, household size, livestock ownership, distance to the nearest market and participation in non-farm activities. The findings of this study suggest that PSNP membership should be reinforced by building household awareness of the benefits of consuming a variety of foods. In addition, PSNP membership should be designed to endow the households to accumulate essential assets, especially livestock.